Lingkungan Kerja di Coffee Shop: Persepsi Barista Terhadap Faktor Pendukung Kepuasan Kerja - Suharni (Mellbaou Publisher, 2025)
Research on baristas' perceptions of the coffee shop work environment is important, considering that a positive work environment can significantly influence employee job satisfaction. This study aims to explore baristas' perceptions of the coffee shop work environment and its impact on job satisfaction. The informants in this study were coffee shop owners and several baristas with diverse work experiences. Data were collected through in-depth interviews using a descriptive qualitative approach. The results indicate that the physical, social, and work policies significantly influence barista job satisfaction. Team support, open communication, and adequate work facilities are the main factors supporting the creation of a positive work environment. This study provides practical implications for coffee shop managers to increase employee job satisfaction through improving the work environment.